COMMUNICATION ASPECTS OF MANAGEMENT WORK ON THE BASIS OF LEADERSHIP - Haliuk, I.B.; Verbovska, L.S. (The actual problems of regional economy development, 2021)
The article is devoted to the study of communication leadership as a tool for effective management in an organization based on the interaction "manager - subordinate". The authors analyze the content of the main categorical terms that underlie communication leadership, namely communication skills and communicative competence, based on which the understanding of the communicative competence of the leader is formed. Based on the details of the main characteristics of communicative competence of the leader, presented in the literature as the work of domestic and foreign theorists and practitioners, and consideration of the specifics of communicative leadership in practical work with a team of authors, the main list of communicative values and similar life positions, the development of skills of joint interaction in team members based on the unity of life views in order to achieve the goals of the organization. The authors identified the specifics of team communication as a determining component in the process of achieving the effectiveness of teamwork and obtaining the desired team results. In particular, the article analyzes the possibility of maximizing the level of effectiveness of interaction "leader - team member" based on the basic postulates that should be used by the leader to enhance interest in communication processes in the team. These postulates include, first of all, the leader's understanding of the desired result of communication, further motivating employees to effective teamwork and communication, understanding the meaning of all processes that take place in the organization. Based on the study, the authors made a number of conclusions, the main one being that the effectiveness of communication leadership is determined by the ability of the leader to systematically perceive the processes in the organization in order to build an adequate communication structure that must meet the organizational structure. Only in this case it is possible to achieve a synergistic effect of communication interaction in the organization.